BANDWIDTH MANAGEMENT TO SET OF INTERNET CONNECTION REFERING FROM STRUCTURAL POSITION USE MIKROTIK RB751-2HnD WITH WEB BASED IN ADISUTJIPTO HIGH SCHOOL TECHNOLOGY - Brama Ady Sulistiyo; Haruno Sajati; Elizabeth Nurmiyati Tamatjita (Compiler, 2014)
Development of information technology and computer networks in particular its services on the one hand facilitate the work of human beings, but as a very widespread internet usage, internet access usage levels become unmanageable. The need for a web-based application that facilitates an admin to manage the bandwidth seems very necessary. By using or utilizing the API (application programming interface) that has been provided by the router is to create a Bandwidth Management Application To Set Internet Connection Referring Structural Position Use Mikrotik RB751G - 2HnD With Web Based In Adisutjipto Technology High School. The results Application test show and prove that bandwidth isn’t right as the transfer rate. As for transfer rate or download speed is not affected by bandwidth rather influenced by the size distribution of the bandwidth paths. Test results also proved that a bandwidth leased from a provider not in accordance with the offer.